Identification of TPACK-ICT Jayapura City High School Biology Teachers in Facing Post-Pandemic Learning - Tanta; Maik Akobiarek; Suriyah Satar; Hanida Listiani; Nurbaya (Jurnal Penelitian Pendidikan IPA, 2023)
TPACK-ICT components by Biology Teachers, this research was carried out with the aim of identifying the Technological Pedagogical Content Knowledge Information and Communication Technology (TPACK-ICT) components of High School Biology Teachers in Jayapura City. The research method used in this research is mixed methods. The sample used in this research was 12 Biology teachers in the city of Jayapura using a sampling technique, namely convenience sampling from the population, namely all teachers of public high schools and private high schools in the city of Jayapura. Quantitative data in this research was obtained using questionnaires using Likert scale 1 to 5 containing 30 statements related to TPACK-ICT with supporting data using an interview guide. The data obtained was then analyzed using quantitative and qualitative approaches. After conducting the analysis, the results showed that the TPACK competency of high school Biology teachers in the city of Jayapura was classified as good for all TPACK components. The average score in each aspect, namely TK, CK, PK, PCK, TCK, TPK, and TPACK is in the medium category, this indicates that biology teachers at Jayapura City High Schools are ready to face post-pandemic learning with their competencies.